Mummified fetus and a pup with eviscerated intestines in a normal litter at term in a Labrador bitch : a case report - CHEEDE, G S; DADARWAL, D; GANDOTRA, V K (The Indian Journal of Animal Reproduction, 2023)
A rare case of canine mummified fetus and a pup with eviscerated intestine in a normal litter at term is reported in tiscommunication.
Keywords: Canine mummification; eviscerated intestine